The Impact of Job Placement on Employee Incompetence - Hasyim; Nuraini (Journal of Management, 2024)
This study demonstrates that organizational commitment is influenced by PT. BPR Hasamitra Makassar's job placement qualities, with a t-test value of 0.000. The results of this study demonstrate a connection between employees' devotion and their workplace. Consequently, employees feel more at ease in their current workplace the more loyal they are to the organization. This study demonstrates that job placement affects employee performance at PT. BPR Hasamitra Makassar, with a sig value on the t-test of 0.000. Accordingly, research on organizational commitment and employee performance at PT. BPR Hasamitra Makassar indicates that a significant t test value of less than 0.04 or 0.000 indicates that employees perform better when they feel at ease in their workplace. This study demonstrates the link between raising corporate commitment and enhancing employee performance. Employees will therefore perform better if they are happy working for the company. As per the Sobel test, the employee performance and job placement are mediated by the organizational commitment variable, as evidenced by the t-calculated value of 5.404, which is more than the t-table value of 1.558. While examining indirect variables yielded a value of 0.324, the direct influence of job placement variables on performance is found to be 0.346